2017
DOI: 10.1097/rti.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Computed Tomographic Technology

Abstract: Cardiothoracic diseases result in substantial morbidity and mortality. Chest computed tomography (CT) has been an imaging modality of choice for assessing a host of chest diseases, and technologic advances have enabled the emergence of coronary CT angiography as a robust noninvasive test for cardiac imaging. Technologic developments in CT have also enabled the application of dual-energy CT scanning for assessing pulmonary vascular and neoplastic processes. Concerns over increasing radiation dose from CT scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Second, this study was done using 128-slice multi-detector CT scanners. Further studies using dual-energy CT scanners and higher multi-detector scanners such as 320-slice detectors are recommended [ 33 , 34 ]. Third, there was no correlation between the results of coronary CTA and conventional angiography.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Second, this study was done using 128-slice multi-detector CT scanners. Further studies using dual-energy CT scanners and higher multi-detector scanners such as 320-slice detectors are recommended [ 33 , 34 ]. Third, there was no correlation between the results of coronary CTA and conventional angiography.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…A potential explanation for these findings is that lowering the CT tube voltage results in a greater photoelectric effect of iodinated contrast media, with only a slight increase in the noise because of improved tube current capabilities. Moreover, the advances in hardware equipped with Stellar detectors and software program in third-generation dual-source CT [ 30 , 31 ], which are supposed to be more sensitive to electron influx, are thus, dose-efficient and generate high quality images while using 80 kVp. A few studies that investigated DECT, showed that the radiation dose was comparable to the single energy 100–120 kVp CT [ 18 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CCTA has become increasingly common in clinical practice as an essential diagnostic component [15][16][17]. Particularly with CT angiographies, increasingly faster acquisition times require…”
Section: Discussionmentioning
confidence: 99%